Effectiveness and Lessons Learned From an Occupational E-Mental Health Intervention for Enhancing Workplace Mental Health: The EMPOWER Cluster Randomized Controlled Trial - de Miquel, Carlota; Van der Feltz-Cornelis, Christina M.; Hakkaart-van Roijen, Leona; Merecz-Kot, Dorota; Sinokki, Marjo; Rodeiro-Boliart, Jordi; Sweetman, Jennifer; Staszewska, Kaja; Vorstenbosch, Ellen; Porricelli, Daniele; Peeters, Stijn; Ayuso-Mateos, José Luis; et al. (JMIR Publications Inc., 2026)
Background:
Occupational e-mental health (OeMH) interventions emerged as a promising solution to prevent common mental health problems and enhance well-being and work performance. However, they must be subject to robust and reliable assessments for effectiveness.
Methods:
A multimodal e-mental health intervention (EMPOWER [The European Platform to Promote Wellbeing and Health in the Workplace]) delivered over 7 weeks was developed and evaluated through a cluster randomized controlled trial conducted mainly in small to medium enterprises and public agencies from Spain (n=127), Finland (n=141), Poland (n=51), and the United Kingdom (n=389) between February 2022 and May 2024 (recruitment finalized in September 2023 and follow-up completed in May 2024). Inclusion criteria were being 18+ years, having a smartphone, sufficient language knowledge, and agreeing to participate. Clusters (companies or departments) were randomized to intervention or control conditions. The primary outcome was presenteeism, and secondary outcomes were depression and anxiety symptoms, etc, all measured at baseline, postintervention, and in 21 weeks after program completion. The analysis was performed as an intention-to-treat approach using adjusted linear mixed models and as per protocol analysis comparing outcomes by level of engagement.
Results:
A total of 347 participants were allocated to the intervention group and 361 to the control group. In the overall sample, the intention-to-treat analysis detected no statistically significant short-term (7 wk) or long-term (21 wk postintervention) effects of the EMPOWER intervention on presenteeism (postintervention β=2.186; 95% CI −2.424 to 6.796, follow-up β=1.294; 95% CI −3.608 to 6.396) and on other secondary outcomes such as depressive symptoms (postintervention β=−0.052, 95% CI −1.02 to 0.905, follow-up β=0.202, 95% CI −0.840 to 1.245), anxiety symptoms (postintervention β=−0.328, 95% CI −1.168 to 0.512, follow-up β=0.375, 95% CI −0.537 to 1.287), or general stress level (postintervention β=0.385, 95% CI −0.195 to 0.965, follow-up β=0.123, 95% CI −0.502 to 0.749). Subgroup analyses yielded several notable results, with significant differences between age groups, gender, and psychological symptoms at baseline. The per-protocol analysis showed no significant differences between participants who actively engaged with the intervention (119/347, 34%) and those who did not. Implementation challenges were related to technical problems, the complexity of this study’s design, external factors, co-design strategy, and organizational barriers, which led to a smaller sample size, high attrition rates, and low adherence.
Conclusions:
Our study provides evidence from a large cluster randomized controlled trial evaluating an OeMH intervention implemented in workplace settings, including small to medium enterprises and public agencies in Europe. Although no overall effectiveness was observed, this study contributes important methodological and implementation insights, highlighting the challenges of evaluating OeMH interventions. These findings suggest that future interventions should prioritize feasibility testing, organizational readiness, user engagement, and more targeted and pragmatic evaluation approaches to enhance real-world impact.